Avatar anthropomorphism and illusion of body ownership in VR - Lugrin, Jean-Luc; Latt, Johanna; Latoschik, Marc Erich (Proceedings of the IEEE Virtual Reality Annual International Symposium, 2015)
In this paper we present a novel experiment to explore the impact of avatar realism on the illusion of virtual body ownership (IVBO) in immersive virtual environments, with full-body avatar embodiment and freedom of movement. We evaluated four distinct avatars (a humanoid robot, a block-man, and both male and female human adult) presenting an increasing level of anthropomorphism in their detailed compositions Our results revealed that each avatar elicited a relatively high level of illusion. However both machine-like and cartoon-like avatars elicited an equivalent IVBO, slightly superior to the human-ones. A realistic human appearance is therefore not a critical top-down factor of IVBO, and could lead to an Uncanney Valley effect.